Tooth loss and associated factors in elders: results from a national survey in Uruguay. (14th October 2015) - Laguzzi, Patricia Nicola; Schuch, Helena Silveira; Medina, Lucy Derrégibus; de Amores, Andrea Rodríguez; Demarco, Flavio Fernando; Lorenzo, Susana
Abstract: Objectives: This study evaluated the prevalence and severity of tooth loss in Uruguayan elders, assessing its association with demographic, socioeconomic, and behavioral factors; the use of health services; and self‐reported dental treatment need. Methods: A population‐based cross‐sectional study was done among Uruguayan individuals of ages 65‐74 years. Data were collected through questionnaires and clinical examinations. The dependent variable, tooth loss, was classified into three distinct outcomes: functional dentition (≥20 teeth), severe tooth loss (<9 teeth), and edentulism. The independent variables were: sex, socioeconomic status, use of health services, hypertension, diabetes mellitus, tobacco use, frequent consumption of alcohol, hygiene habits, and need for dental care. Results: The sample comprised 341 individuals, and the mean number of teeth present was 9.73 (95% confidence interval, 8.77‐10.69) for each individual. After multivariate analysis, lack of a functional dentition, severe tooth loss, and edentulism were found to be associated with lower socioeconomic level, frequent consumption of alcohol, and receiving treatment from the public health system ( P  < 0.05). Individuals with self‐reported dental treatment need had more severe tooth loss and presented a higher degree of edentulism ( P  < 0.05). Conclusions: There is a high and severe prevalence of tooth loss in elderly Uruguayans, especially among those from lower socioeconomic levels. Our findings highlight the importance of public health policies to prevent and treat tooth loss.